COMPLAINING EXPRESSIONS USED BY THE CHARACTERS IN THE MOVIE ENTITLED TWO WEEKS NOTICE: A PRAGMATICS STUDY - Firman Ramdani; Lia Maulia Indrayani Maulia Indrayani (Eltin Journal : Journal of English Language Teaching in Indonesia, 2018)
The study of complaining expressions used by the characters in the movie entitled “Two Weeks Notice” has been done. The object of this study is utterances that contain complaining expression.  The aims of this study are to analyze and describe strategies of complaint and their functions. This study employs a descriptive qualitative method.  This study applies the complaint theory proposed by Trosborg (1995) and the context theory proposed by Mc Mannis et al (1987). The result of this study shows that all of complaint strategies according to Trosborg can be found in this movie, those are hint, annoyance, ill cosequence, indirect accusation, direct accusation, modified blame, explicit condemnation of the accused’s action, and explicit condemnation of the accused as a person strategies. There are three functions of complaint found in this movie, those are to break a relationship or create a social distance among the participants, to maintain a relationship and fix a situation, and to show a negative feeling or share a specific negative evaluation.